2021
DOI: 10.1029/2020gl092138
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic 3D Navier‐Stokes Flow in Self‐Affine Fracture Geometries Controlled by Anisotropy and Channeling

Abstract: This study presents a probabilistic analysis of 3D Navier‐Stokes (NS) fluid flow through 30 randomly generated sheared fractures with equal roughness properties (Hurst exponent = 0.8). The results of numerous 3D NS realizations are compared with the highly simplified local cubic law (LCL) solutions regarding flow orientations and regimes. The transition between linear and nonlinear flow conditions cannot be described with a generally valid critical Reynolds number (italicRecrit), but rather depends on the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…By examining the distributions of D v in Figure 8 along with the velocity magnitude distributions in Figure 4, we found that a majority of the misprediction took place in regions of low velocity/flow especially near the wall and contact boundaries (Egert et al., 2021; Zou et al., 2017). As the low‐flow regions generally contribute less to the overall flow behaviors of the fracture, the large misprediction of local velocity in these regions may still represent weak impact on the overall fracture transmissivity.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…By examining the distributions of D v in Figure 8 along with the velocity magnitude distributions in Figure 4, we found that a majority of the misprediction took place in regions of low velocity/flow especially near the wall and contact boundaries (Egert et al., 2021; Zou et al., 2017). As the low‐flow regions generally contribute less to the overall flow behaviors of the fracture, the large misprediction of local velocity in these regions may still represent weak impact on the overall fracture transmissivity.…”
Section: Resultsmentioning
confidence: 98%
“…One reason may be that these local-scale approximations have not been widely appreciated due to a lack of comprehensive evaluation of their performances in describing fluid flow in complex fracture voids under subsurface stresses. Although later works have also evaluated individual local-approximation such as in Egert et al (2021), the latest systematic evaluation of various local-scale approximations was perhaps done by Konzuk and Kueper (2004). In their work, transmissivity obtained from applying different local-scale approximations was compared with that from fracture flow experiments.…”
mentioning
confidence: 99%
“…Egert et al. (2021) were able to demonstrate the need for solving the NSE to consider both the three‐dimensional fracture void space and growing nonlinear effects in the small‐scale fracture‐internal flow field by comparing NSE and LCL for Reynolds numbers up to 220. The natural small‐scale flow field in a fracture is not homogeneously distributed.…”
Section: Introductionmentioning
confidence: 99%
“…The solution of the nonlinear Navier-Stokes equations (NSE) on rough fracture surfaces allows to circumvent these limitations, but they are rarely used due to high computational complexity (Javadi et al, 2014;Liu, He et al, 2020) and are mostly limited to small Re (Aghajannezhad & Sellier, 2022;He et al, 2022). Egert et al (2021) were able to demonstrate the need for solving the NSE to consider both the three-dimensional fracture void space and growing nonlinear effects in the small-scale fracture-internal flow field by comparing NSE and LCL for Reynolds numbers up to 220. The natural small-scale flow field in a fracture is not homogeneously distributed.…”
mentioning
confidence: 99%
“…Open fractures are primary conduits for groundwater flow and thus constitute preferential transport pathways for dissolved contaminants. Fracture internal variability, caused, for example, by shearing, leads to significant variability in the in‐plane groundwater velocity field (Egert et al., 2021; Zou et al., 2017), which in turn affects mass exchange processes with the stagnant water in the bordering porous rock matrix (Trinchero, Poteri, et al., 2020). Fracture filling minerals, that might have precipitated during past hydrothermal events, add more pieces to this already complex puzzle.…”
Section: Introductionmentioning
confidence: 99%